Starts - McCauley, W.
Author explains a swimming start which is to be practiced only in a deep pool and under the supervision of a coach, and only one person in the lane at a time. Many races are lost on the starting block or the dive into the water.There are three distinct phases of the start explained here, the starting block technique, the dive into the water and the pullout or breakout.